Comparison on the quality performance achievement of students in UiTMCPP during the ODL and F2F teaching and learning methods / Lyly Nyl Ismail, Norsabrina Sihab and Noor Aina Abd Razak - Ismail, Lyly Nyl; Sihab, Norsabrina; Abd Razak, Noor Aina (Universiti Teknologi MARA, Pulau Pinang, 2022)
Lockdowns in response to the spread of COVID-19 in 2020 have interrupted the conventional Teaching and Learning (T&L) approach in educational institutions. In conjunction with that, higher education was quick to replace face-to-face (F2F) lectures with fully online learning (OL). The abrupt change impacted learning and examinations across the globe. To remain relevant, universities have reinvented and expanded the digitalization in T&L. This paper investigates the impact of student's performance against the changes in the teaching and learning (T&L) methods from traditional F2F to OL and online distance learning (ODL) during the COVID-19 pandemic in Universiti Teknologi MARA, Cawangan Pulau Pinang (UiTMCPP), Malaysia. Data collected in this study was based on the examination results in both the Diploma and Degree students from the year 2019 to 2020 which involved four consecutive semesters: two semesters on F2F and two semesters on ODL. The examination results were projected into the Key Performance Indicator (KPI) that was determined by the top management in UiTMCPP - Student Quality Objectives (OKP). The main purpose of OKP is to monitor the student's performance and achievement in every programme offered. The statistical analysis was conducted using the Statistical Package for Social Science (SPSS). The results of Analysis of Variant (ANOVA) and Tukey Honest Significant Difference (HSD) show that the T&L method is significantly different between F2F and ODL, whereby the ODL method significantly improved the students' performance.